Copper-catalyzed multi-component reactions synthesis of nitrogen-containing polycyclic compounds - Ohta, Yusuke; SpringerLink (Online service). (Berlin Heidelberg New York Springer, 2011)
A copper-catalyzed direct synthesis of 2-(aminomethyl)indoles by catalytic domino reaction including multi-component coupling was developed, and is the first example of a three-component indole formation without producing salts as a byproduct. Based on this reaction, a copper-catalyzed synthesis of 3-(aminomethyl)isoquinoline was accomplished which represents an unprecedented isoquinoline synthesis through a four-component coupling reaction. Following these results, extensive application studies using one-pot palladium-, acid-, or base-promoted cyclization revealed that indole- or isoquinoline-fused polycyclic compounds can be readily synthesized through multi-component reactions. As the concept of Green Chemistry becomes ever more important, these findings may provide efficient and atom-economical approaches to the diversity-oriented synthesis of bioactive compounds containing a complex structure. This could lead to development of promising drug leads with structural complexity. The work of this thesis will go on to inspire the synthetic research of many readers.
Electronic reproduction.
Keywords: Organonitrogen compounds; Polycyclic compounds -- Synthesis; Electronic books